KONTRIBUSI KONSEP DIRI TERHADAP MOTIVASI BELAJAR MAHASISWA BIMBINGAN KONSELING - Wibowo, Agus (JURNAL KONSELING GUSJIGANG, 2017)
The motivation of learning is an encouragement from internal of  the individual for learning activities. Students have a critical and idealistic priciple, must have a high motivation learning, it is because they have the choice for his life.. But the reality the students is low of the motivation learning, , and they are always to late do the task. The condition is may be is have contribution from  the self-concept of the students. The purpose of the study is to views the self concept contribute, learning motivation, and the contribution of self concept to the learning motivation student of guidance and counseling  University Muhammadiyah Metro. The research method used is correlation method, The research population is 310 students, and technique of sampling using proporsioanal random sampling, and the number of sample is 175 students. The analysis technique used data product moment. The result showed that the students  of guidance and counseling  university Muhammadiyah Metro was in medium category, and motivation was in medium criterion. Thus, the result of research is self concept to contribute positive and significant  to the  motivation learning student of guidance and counseling  University Muhammadiyah Metro